Changing social-class distribution of heart disease. Issue 6145 (21st October 1978) - Marmot, M G; Adelstein, A M; Robinson, N; Rose, G A
Abstract : Analysis of mortality trends over 40 years in England and Wales showed that mortality from coronary heart disease had become progressively more common in working-class men and women than in those from the middle and upper classes. The change was most noticeable for men. Whereas in 1931 and 1951 heart disease was more common in men of social classes I and II, by 1961 it was more common in men of classes IV and V. This change in social-class distribution can only partly be explained by changes in diagnostic methods. The worsening mortality of classes IV and V correlated with relatively more smoking, a higher consumption of sugar, and a lower consumption of wholemeal bread in these classes. There was no correlation between change in heart disease and change in the social-class pattern of fat consumption.